Production of Sugar from Cassava Peel using Different Chemical Pre-treatment - Nuha Aqilah Zulkifli; Latiffah Karim (USIM Press, 2024)
Malaysian Journal of Science, Health & Technology (MJoSHT) Volume 9 No.2 Page (136-146)